KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VII SMP NEGERI 1 SASAK RANAH PASISIE KABUPATEN PASAMAN BARAT DENGAN TEKNIK MENJAWAB PERTANYAAN - Lestari, Defa Juli; Eska, Wirnita; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
Ability Reading Comprehension Seventh Grade Students of SMP Negeri 1 Sasak Ranah Pasisie West Pasaman Regency with Questions Answering. This research is quantitative descriptive method. The study population was all students in class VII SMP Negeri 1 Sasak Ranah Pasisie by the number of students 141 people. Sample this reseach was 30 people on the number of students, is the class VII2, because it represents a sample taken using purposive sampling technique. The instrument used is objective test with answer technical questions.Based on the data analysis and discussion described in chapter IV some conclusions can be drawn, namely: (1) reading comprehension class VII student of SMP Negeri 1 Sasak Ranah Pasisie West Pasaman with the technical of questions answering for the content of reading comprehension indicators classified as More Than Enough (LDC) with a mean of 74.5 rounded to 74 contained in the range of 65-75 %. (2) reading comprehension class VII student of SMP Negeri 1 Sasak Ranah Pasisie West Pasaman with the technical the questions answering for appropriateness indicator reading the contents classified as Good (B) with a mean of 79.6 rounded to 79 contained in the range of 76-85 %. (3) the ability of reading comprehension class VII student of SMP Negeri 1 Sasak Ranah Pasisie West Pasaman with the technical of answering questions for both indicators classified as Good (B) with a mean of 77 contained in the range of 76-85 %.Relevant to this, the researchers put forward several suggestions, which are as follows: First, that students of class VII SMP Negeri 1 Sasak Ranah Pasisie more reading so that it can increase knowledge. Second, in order to subject teachers Indonesian language and literature at SMP Negeri 1 Sasak Ranah Pasisie further improve the learning techniques of variation in reading comprehension.Â